2008
DOI: 10.1375/twin.11.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Relationships in Atopy: A Review of Twin Studies

Abstract: The genetics of asthma and atopy has been studied frequently in twin populations from various parts of the world. However, emphasis has been put on univariate analysis of questionnaire data, whereas clinical and intermediate traits only sporadically have been studied, especially in multivariate settings. This review focuses on multivariate twin studies of atopy and related traits. We conclude that the genetic liability to most atopic traits is significantly correlated but that trait-specific genes also play a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 65 publications
2
20
0
Order By: Relevance
“…Earlier twin studies among children from Scandinavia and other countries have found that the risk of asthma in MZ twins is increased approximately 5-fold relative to the background population, whereas the risk in DZ twins is increased approximately 2-fold [36]. These findings are consistent with a substantial genetic component for asthma with a heritability contribution of around 70%.…”
Section: Twin Studies Of Asthmasupporting
confidence: 66%
“…Earlier twin studies among children from Scandinavia and other countries have found that the risk of asthma in MZ twins is increased approximately 5-fold relative to the background population, whereas the risk in DZ twins is increased approximately 2-fold [36]. These findings are consistent with a substantial genetic component for asthma with a heritability contribution of around 70%.…”
Section: Twin Studies Of Asthmasupporting
confidence: 66%
“…Twin and family studies are widely used to estimate genetic and environmental contributions to atopic disease [5,6]. The multivariate classical twin design can help to estimate the degree to which the same genetic and environmental factors influence different intermediate phenotypes [7].…”
mentioning
confidence: 99%
“…If there is overlap in genes for two traits it is expected that the cross-twin cross-trait correlation will be higher in monozygotic (MZ) twins than in dizygotic (DZ) twins for these traits. Using this information cannot only widen our understanding of atopic comorbidity, it can also enhance gene-mapping efforts [6] and consequently enable us to understand the interplay between different pathways underlying asthma, benefitting the discovery of targeted treatments and interventional measures.…”
mentioning
confidence: 99%
“…Twin studies have been a valuable source of data to examine the role of genetics in monozygotic (MZ) compared with dizygotic (DZ) twins and have provided support for the hypothesis that allergic disorders have a genetic predisposition [8,9]. Clarke et al [10] found an increased association within MZ twins compared to within DZ twins for asthma (MZ: OR, 25.6; 95% CI, 11.3-57.8 vs DZ: OR, 1.9; 95% CI, 1.0-3.5), allergen sensitization (MZ: OR, 14.6; 95% CI, 7.1-30.1 vs DZ: OR, 2.5; 95% CI, 1.4-4.5), and bronchial hyperreactivity (MZ: OR, 14.1; 95% CI, 6.4-31.0 vs DZ: OR, 4.2; 95% CI, 2.1-8.6).…”
Section: Twin Studiesmentioning
confidence: 99%
“…The data regarding specific IgE inheritance are increasingly complex, with some twin studies suggesting that overall atopy is under stronger genetic control than sensitization to individual allergens [9]. Wuthrich et al [11] found that concordance rates were not significantly different between the skin prick test results of 30 MZ and 20 DZ twin pairs when they were tested for 7 different allergens (D. pteronyssinus, Timothy grass, birch, hazel, dogs, cats, and horses).…”
Section: Twin Studiesmentioning
confidence: 99%